The Pengaruh Soft Total Quality Management (TQM) terhadap Kepuasan Kerja dan Kinerja Karyawan pada Perusahaan Minyak dan Gas - Andi, Khairunnisa; Khairunnisa, Andi; Ratum, Athina Sakina (Universitas Katolik Parahyangan, 2025)
The rapid economic and industrial expansion has led to increased global corporate competitiveness, forcing organizations to constantly improve their effectiveness and sustainability. Total Quality Management (TQM) is recognized as a process that enhances individual and organizational performance, competitive advantage, and customer satisfaction. Despite its recognized value, the implementation of soft TQM practices remains underexplored in high-risk and heavily regulated sectors such as the oil and gas industry, especially within the Indonesian. PT XYZ, an oil and gas company in Indonesia, has implemented TQM. However, the company continues to face operational issues including unmet departmental targets and the lack of implementation of essential work-related innovations. This study investigates the influence of soft TQM on Employee Job Satisfaction (EJS) and Employee Performance (EP), and examines EJS as a mediating variable. Data were collected through questionnaires using a Likert scale and analyzed using PLS-SEM with SmartPLS 4. The results indicate that soft TQM significantly and positively affects both EJS and EP, and that EJS significantly mediates the relationship between soft TQM and EP. The study contributes to TQM theory by extending its application to an underrepresented industrial and national context, and by emphasizing the importance of human-centered practices in improving individual performance outcomes. It also highlights the need for tailored quality strategies to address challenges such as workforce diversity, operational complexity, and innovation implementation in the oil and gas sector.